Gestión municipal y desarrollo local - Tapia-Aguirre, Juan (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented to the Universidad Nacional Micaela Bastidas de Apurímac, which aimed to determine the relationship between municipal management and local development, from the perception of the residents of the district of San Pedro de Cachora (Peru), whose type of research corresponds to the basic study, non-experimental design and in particular to the correlational descriptive design. The study population consisted of 908 residents registered in the four communities in 2018, which make up the district of Cachora, in relation to the aforementioned population universe, a sample of 270 residents was taken, under the simple random sampling procedure. The instrument applied was the questionnaire and the technique used to collect information was the survey. The results reached were that 13.3% of the population perceive municipal management as very bad while 64.4% perceive it as bad. Likewise, 7% of the population perceives local development as very bad while 44.4% perceives it as bad, for which a favorable result was obtained in the general hypothesis, with a Spearman's Rho of 0.638, evidencing a medium to considerable positive relationship. in relation to the study variables and a p value = 0.000, so it is concluded that there is a significant relationship between municipal management and local development of the district of San Pedro de Cachora, 2021.